Sequence conservation of apolipoprotein A-I affords novel insights into HDL structure-function - Bashtovyy, Denys (The American Society for Biochemistry and Molecular Biology, 2011)
We performed alignment of apolipoprotein A-I (apoA-I) sequences from 31 species of animals. We found there is specific conservation of salt bridge-forming residues in the first 30 residues of apoA-I and general conservation of a variety of residue types in the central domain, helix 2/3 to helix 7/8. In the lipid-associating domain, helix 7 and helix 10 are the most and least conserved helixes, respectively. Furthermore, eight residues are completely conserved: P66, R83, P121, E191, and P220, and three of seven Tyr residues in human apoA-I, Y18, Y115, and Y192, are conserved. Residue Y18 appears to be important for assembly of HDL. E191-Y192 represents the only completely conserved pair of adjacent residues in apoA-I; Y192 is a preferred target for site-specific oxidative modification within atheroma, and molecular dynamic simulations suggest that the conserved pair E191-Y192 is in a solvent-exposed loop-helix-loop. Molecular dynamics testing of human apoA-I showed that M112 and M148 interact with Y115, a microenvironment unique to human apoA-I. Finally, conservation of Arg residues in the α11/3 helical wheel position 7 supports several possibilities: interactions with adjacent phospholipid molecules and/or oxidized lipids and/or binding of antioxidant enzymes through cation-π orbital interactions. We conclude that sequence alignment of apoA-I provides unique insights into apoA-I structure-function relationship.